„Doch das bei weitem schwierigste Ehehindernis ist das der Verwandtschaft“: Forbidden Marriage Between Incest Taboo and the Fortune of the Noble Family in 17th-18th-Century Germany - Schraut, Sylvia (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
During the 17th and 18th century the German nobility called a planned marriage a pro-ject of marriage, because marriages had a long phase of planning, in which more then two people were involved. Noble projects of marriage had at least the function to create ever-lasting friendship between two noble families. This custom was part of the economic and po-litical strategies of the families involved and had often effects on the development of whole territories. Noble projects of marriage consequently concerned the family law as well as the law of the nobility and the church. I shall discuss the strategies of marriage of a special social group, the so-called Cath-olic German Reichsritterschaft during the 17th and 18th centuries. This noble group was re-garded as a strong partner of the German Imperial Catholic Church, the Reichskirche. Last but not least its members owed their remarkable political careers to the Church, but their idea of marriage were never-the-less in opposition to the canonical marriage laws; in fact, in planning exactly these political careers, which they owed to the Church, their concept of marriage clashed with the impediments to marriage that too close kinship posed. My paper aims at ana-lysing the marriage law of the Church as a papal instrument of influence over this special group of nobles.